Crystallization and preliminary X-ray crystallographic studies of the N-terminal domain of human ribosomal protein L7a (RPL7a) - Jang, Tae-ho (International Union of Crystallography, 2011)
Ribosomal proteins are a major component of ribosomes, which catalyze protein synthesis. One ribosomal protein, L7a (RPL7a), which is a component of the 60S large ribosomal subunit, has additional functions involved in cell growth and differentiation that occur via interaction with human thyroid hormone receptor (THR) and retinoic acid receptor (RAR) and in turn inhibit the activities of the two nuclear hormone receptors. In this study, the N-terminal domain of human RPL7a was overexpressed in Escherichia coli using an engineered C-terminal His tag. The N-terminal domain of human RPL7a was then purified to homogeneity and crystallized at 293 K. X-ray diffraction data were collected to a resolution of 3.5 Å from a crystal belonging to the tetragonal space group P4(1)22 or P4(3)22 with unit-cell parameters a = 92.28, b = 92.28, c = 236.59 Å.